Response of Agriculture Production to Change of Foreign Direct Investment and Public Agriculture Expenditure in South Africa: A Monte Carlo Simulation Analysis - Mbiakop, William Djamfa; Khobai, Hlalefang; Fani, Djomo Choumbou Raoul (International Journal of Economics and Financial Issues, 2023)
The rationale of this paper was to investigate the response of agriculture production to the simultaneous shock of foreign direct investment and public agricultural spending in South Africa during 1991-2019. Data were collected from secondary sources and analyzed using Monte Carlo simulation. Results revealed that agriculture production is maximized at 1,73% if Foreign direct investment inflows, agricultural credit, and the number of employees increase by 10% while public spending is decreased by 10%. Hence, it is recommended that policymakers should combine FDI inflows in agriculture, and agricultural credit in a complementary manner, with emphasis to attract more extensive farm workers to ensure the sustainability of production in the agriculture sector in South Africa. This paper contributes to enhance agriculture sector by using the best combination of input in agriculture in order to maximize production.